Applications of 3D printers in prosthesis development for prosthetic replacement surgery (Artoplasties) (arthroplasties). Use in canines - Gutiérrez-Sandí, William (2018)
The technology of 3D printing offers several benefits for all the ambits in which the human being develops, from the fabrication of home objects like chairs, drinking glass, dishes, tables, etc. to the health sciences allowing the elaboration of prosthetic pieces for both human and animals.Such technology has been analyzed in this report to known the viability of making prosthetic pieces for canine animals. In this explorative report were documented the several machines (3D printers, computers, etc.) and materials (polymers, resins, metal, etc.) that are required to be able to make the 3D impressions and were also analyzed real cases in which the 3D printed prosthesis were already implemented. The scientific method was used for the planning and development of this investigation and its results allowed a deeper understanding about this technology and its applications on animal health, just as they allowed to known with resources are necessary to be able to implement it.